PENANGANAN PEDAGANG KAKI LIMA DI KOTA MAKASSAR - H. Mustafa Hasbar (AkMen JURNAL ILMIAH, 2008)
Formal Sector represent the sector which play role important in good Indonesia economics in this time and also in a period to coming because easy in character entered the easy to enter the. The important role shown by fact that informal sector in Indonesia in the year 2005 permeating more or less 60 percentage of entire all labor force in Indonesia. This number consistently can be perceived from year to year may even exist tendency to go up. microly is its his important is informal sector role can be perceived from ability of Cloister Merchant ( PKL) provide the goods and service which cheap relative so that can be accessed by society widely especially from economic faction lower. But, the mentioned cannot meniadikan view which is leaving for each other the back cause the government of Town Makassar have to take the policy having the character of to duplicate the ( Double Standard). In one side of Pemetintah Town do conduct the construction to informal sector and make hay through retribution for example, but on the other side Town Government also conduct the enjoinment and dissipating of because damage reason of town image and police the public. This matter have caused the informal sector is angle;corner on course which marginal always pulled over and always become in trouble Set Of Police of Pamong District public service.